Design of reinforced concrete rectangular cross-sections according to the second generation of Eurocode - Željko Smolčić; Davor Grandić; Paulo Šćulac (Građevinar)
This paper describes the design procedure for reinforced concrete rectangular cross-sections according to the standard FprEN 1992-1-1 (second generation of Eurocode 2). Design was carried out in two ways: using design tables for reinforced concrete rectangular sections and using a direct analytical procedure. The stress-strain diagram in the form of a parabola-rectangle was used for concrete, while for the reinforcing steel a bilinear stress-strain diagram with a horizontal post-elastic branch without strain limit was applied. For this reason, when designing the reinforced concrete cross-section, it is necessary to limit the strain in the compression zone of the concrete. Tables for the design of reinforced concrete rectangular sections were obtained using a new procedure in which the mechanical reinforcement ratio is varied. A direct analytical procedure was used for comparison, which can be used for the design of reinforced concrete rectangular sections without the need to use tables. The limit values of the coefficient of the height of the compression zone for pure bending were calculated according to the standard FprEN 1992-1-1.